2017
DOI: 10.1108/jfra-11-2015-0099
|View full text |Cite
|
Sign up to set email alerts
|

The effect of disclosure regulation on the bias and accuracy of management earnings forecasts in Malaysian IPO prospectuses

Abstract: Purpose This paper aims to examine the impact of disclosure regulation on the levels of bias and accuracy in management earnings forecasts disclosed in the prospectuses of Malaysian initial public offering (IPO). Specifically, the authors investigated the two environments of regulation (mandatory versus voluntary) to draw some conclusions regarding the benefits of regulating disclosure of management earnings forecasts. Design/methodology/approach A sample of 111 Malaysian IPOs listing on the Main Market of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
26
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 45 publications
6
26
2
Order By: Relevance
“…This figure for Indonesia is far lower compared to other countries. Like the mean forecast error reported for Bangladesh 48 percent (Karim, Ahmed, & Hasan, 2013), Greece 39.72 percent (Boubaker et al, 2016), Thailand 35.76 percent (Lonkani & Firth, 2005), Australia 34.49 percent (Firth, Gounopoulos, & Pulm, 2012) and Malaysia 23.76 percent (Amer & Ahmad-Zaluki, 2017). On the other hand, the lower mean forecast error rates were found in Hong Kong 7.26 percent (McGuinness, 2005), Singapore 10.4 percent (Firth et al, 1995), Great Britain 10.70 percent (Jelic, 2014) and New Zealand 11.10 percent (Firth, 1997).…”
mentioning
confidence: 53%
See 3 more Smart Citations
“…This figure for Indonesia is far lower compared to other countries. Like the mean forecast error reported for Bangladesh 48 percent (Karim, Ahmed, & Hasan, 2013), Greece 39.72 percent (Boubaker et al, 2016), Thailand 35.76 percent (Lonkani & Firth, 2005), Australia 34.49 percent (Firth, Gounopoulos, & Pulm, 2012) and Malaysia 23.76 percent (Amer & Ahmad-Zaluki, 2017). On the other hand, the lower mean forecast error rates were found in Hong Kong 7.26 percent (McGuinness, 2005), Singapore 10.4 percent (Firth et al, 1995), Great Britain 10.70 percent (Jelic, 2014) and New Zealand 11.10 percent (Firth, 1997).…”
mentioning
confidence: 53%
“…Research on earnings forecasts by Amer & Ahmad-Zaluki (2017) concluded that earnings forecasts are quite relevant for shareholders. Earnings forecasts from management have a high probability to be used as a guide in making investment decisions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies on the structure of board of directors failed to provide a complete perception of the board of directors as the primary responsible mechanism to enhance the earnings forecasts of the firms. Therefore, this study is an attempt to extend and support prior studies' findings and explanations (Ahmad-Zaluki & Wan Hussin, 2010;Bédard et al, 2008;Ammer & Ahmad-Zaluki, 2017) on the topic, as it furnishes evidence on the influence of the board of directors characteristics on the accuracy of management earnings forecasts.…”
Section: Introductionmentioning
confidence: 60%